(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The Sahel-region is facing a major crisis that we hardly seem to notice, because the conflicts in Ukraine and Gaza are drawing much more of our attention. It is not only a pity, but also could turn out to be a strategic mistake. The stability in the region is strongly affected by jihadist motivated movements, such as Islamic State (IS). In addition, there are geopolitical influences in the region, such as Russian involvement e.g., that are not necessarily adding to better stability. In the period 2022-2023 I was the Force Commander in the Mission Multidimensionnelle Intgre des Nations Unies pour la Stabilisation au Mali (MINUSMA). Although the mission was mandated for Mali, the situation in Mali cannot be seen separate from the increasing problems in the entire Sahel-region. In this article I will share my views on lessons we can draw from MINUSMA especially in the context of the UNs work on the future of peacekeeping. I sincerely recognize the fact that I cannot be extensive and I also strongly voice upfront that we should do thorough in-depth analysis on all the lessons coming from MINUSMA before drawing conclusions. The UN has taken care of the latter with an independent study The Future of Peacekeeping, New Models, and Related Capabilities published in November 2024. This study was a starting point for a trajectory leading up to a ministerial conference 13-14 May this year on the Future of UN Peacekeeping. MINUSMA unfortunately has ended in December 2023 because the Malian government has asked the UN to end the mission. I will first say a few words about the complexity of the situation in Mali, followed by the background of the UN mission MINUSMA and its mandate. After that I will discuss some relevant lessons emerging from my experience as Force Commander, before giving my thoughts on the future of peacekeeping.